Designing fair compensation for compulsory acquisition of land: Empirical estimation of hope value, blight, and the negative impact of landowners' caste on the value of land in Bengaluru (India) - Jyoti Rao (Asian Development Bank Institute (ADBI), 2019)
Public agencies often rely on their power of compulsory acquisition of privately owned land when it comes to procuring land for large infrastructure projects. Over the years, the process of compulsory acquisition has evolved to compensate the affected landowners better, to the extent of paying additional monetary compensation or solatium. For example, according to the most recent improvements made to the Indian legislature on compulsory acquisition of land, the acquiring agency should make an additional payment of two to four times the original market value of land to the affected landowner. This is the polity and law's indirect acknowledgment that fair compensation extends beyond the market value of land, although there is less clarity on the theoretical and empirical justification for the same. There is an existing body of literature, such as "Functionings of Land" by Rao (2018), that has applied Sen's capability theory to explain the value of land as a cumulative value of usefulness (or functionings) for its owner, of which the monetary value is only one functioning. While there are many non-monetary functions of land, which deserve compensation, this research limits the scope of the discussion to measurable monetary losses associated with land. Advancing the discussion on adequate monetary compensation for the affected landowners, this research argues that compensation extends beyond the market value of land to include other forms of financial losses that compulsory acquisition imposes, such as (i) the loss of financial benefits accruing from improvement in land use in the future (or the "hope value" of land), which ranged between 39% and 527% in the case of the Bangalore-Mysore Infrastructure Corridor (BMIC) project; and (ii) the reduction in land value due to acquisition notification, which amounted to approximately 31% in the case of the BMIC project in India. In addition to these objective losses, which are common across all landowners, there are person-specific characteristics that influence the market value of land. For example, research has found that the landowners' lower caste negatively affected the value of land around the BMIC project. This reduction could be a joint outcome of the legal protection of ownership rights of Scheduled Caste/Scheduled Tribes (which curtails purchase by non-SC/STs) and the lack of bargaining power due to the lower social status of SC/ST landowners. The above findings suggest that a fair compensation model extends beyond the market value of land to take account of the comprehensive value of land to its owner, and it is possible to derive this as a joint function of personal and land characteristics.
Keywords: Q15; R32; 330; hope value; land value; compulsory acquisition; compensation; land functionings